Genetic divergence among Corylus colurna genotypes based on morphological characters of hazelnut - Srivastava, Kanchan; Zargar, Khurseed; Singh, Shyam (Biodiversity: Research and Conservation, 2011)
Genetic divergence was studied in 41 genotypes of Corylus colurna on the basis of 15 morphological characters of nuts. The divergence among genotypes was estimated by the Mahalanobis' method and the studied genotypes were grouped into clusters by Tocher's method. The obtained data were analysed using the PCA and CA. As a result, 9 genotype clusters were distinguished and a wide diversity among genotypes originating from the same locality was found. It has been proposed that for obtaining the most desirable transgressive segregates in Corylus colurna, genotypes from the genetically most distant clusters should be crossed.